IMPROVING THE TECHNICAL APPROACH TO MANAGING THE PROCESS OF LOCAL TREATMENT OF DRAINAGE RUNOFF FROM IRRIGATED LANDS - Drovovozova Tatyana I.; Kirilenko Andrey A. (Мелиорация и гидротехника, 2023)
Purpose: substantiation and development of the facility design for local treatment of drainage runoff discharged from an irrigated area. Materials and methods. The study was carried out on the example of a representative object – a collection-discharge (drainage) well of a collector-drainage network located on an irrigated site of the Nizhne-Donskaya irrigation system of the Rostov region. The source materials were the results of field studies of the hydrochemical parameters of drainage water in the well and the central collector. Results and discussion. Since the drainage water quality in the drainage well is much higher than in the mouth of the central collector, the reconstruction of the well will allow effective treatment of low drainage flow rates with minimal financial costs. The proposed design is based on dividing the collector-drainage network into areas with their respective wells, on the outgoing collector pipes on which devices for drainage runoff treatment are mounted. The principle of the device is based on the use of removable cartridges filled with various filter materials, depending on the quality of the treated drainage flow. For example, for water desalination, it is recommended to use loads from ion-exchange resins (cation exchanger, anion exchanger). The example shows that cleaning from the main salt-forming ions of drainage flow with a flow rate of 7 m³/month will require 39.5 liters of cation exchanger and 89.3 liters of anion exchanger, this will amount to 31.7 thousand rubles. Conclusions. The use of drainage wells as local treatment facilities will improve the ecological situation in the zone of irrigated agriculture, distribute responsibility between agricultural producers and owners of reclamation systems for the quality of drainage flow discharged into natural water bodies. The proposed design will provide a multi-variant operation of the device for drainage runoff treatment due to combinations of filter media and sets of various removable cartridges.